The influence of age and captivity on cardiac structure and function in rhesus macaques - T. G. Dawkins; B. A. Curry; A. Drane; V. N. Rivas; Y. Ueda; J. A. Stern; D. Philips; J. Negron-Del Valle; Lauren Brent; James Higham; Angelina Ruiz-Lambides; Noah Snyder-Mackler; et al. (GeroScience, 2026)

Physiological and Transcriptomic Insights into Mechanisms of Salt Tolerance in the Leaves and Roots of the Halophyte Suaeda japonica Makino Under High Salinity Stress - Shinta; Kristine Mae Y. Bentoy; Anisa Nazera Fauzia; Mami Nampei; Nguyen Manh Linh; Akihiro Ueda (Journal of Plant Growth Regulation, 2026)
Suaeda japonica Makino, a succulent euhalophyte from the Chenopodiaceae family, grows naturally in Japan and is presumed to exhibit high salt tolerance. However, the molecular mechanisms underlying its salinity tolerance remain poorly understood. This study aimed to examine the physiological responses of S. japonica to varying NaCl concentrations, perform transcriptome profiling of its leaves and roots under 600 mM NaCl exposure, and identify key genes involved in salt tolerance. S. japonica exhibited remarkable tolerance to extreme salinity levels of up to 600 mM for 28 days. Physiological analysis revealed that salinity stress led to increased Na + , soluble sugars, and proline; increased antioxidant enzyme activities; and decreased malondialdehyde (MDA) concentrations in the leaves, indicating a protective role for osmotic regulation, reactive oxygen species (ROS) scavenging, and protection of cellular macromolecules in S. japonica under high salinity. De novo RNA-seq analysis detected 8695 and 9424 differentially expressed genes (DEGs) in the leaves and roots, respectively. Salinity-responsive transcription factors including bHLH, AP2-EREBP, bZIP, WRKY, NAC, HSF, and MYB have been identified. Additionally, DEGs related to the ABA signaling pathway, ion channels/transporters, Ca 2+ signaling, aquaporins, ABC transporters, starch and sucrose metabolism, proline biosynthesis, LEA proteins, and ROS scavenging were significantly expressed in both the leaves and roots, suggesting that these may be the major protective mechanisms to high salinity stress in S. japonica . This study provides a new perspective on the molecular mechanisms underlying salinity tolerance in S. japonica and establishes a foundation for future research.

Stenotrophomonas sp. strain CK1 volatile organic compounds improved rice growth under saline conditions - Kristine Mae Y. Bentoy; Shinta; Mami Nampei; Akihiro Ueda (Theoretical and Experimental Plant Physiology, 2025)
Plant-bacteria indirect interaction is a naturally occurring phenomenon however many aspects of this interaction remain unclear. In this study, the effects of bacterial inoculation were investigated by tissue culture experiments as indirect application to compare rice growth in saline conditions. Four isolates applied indirectly had 1.5-times greater shoot dry mass of rice under 100 mM NaCl treatment. The isolates were identified using 16S rRNA sequencing, with sequences of type strains from the genus Stenotrophomonas aligned using MEGA11, followed by model testing and phylogenetic tree construction. HS-SPME/GC–MS experiment was performed to identify the microbial volatile organic compounds that possibly contribute to the effect of indirect application. A total of 23 compounds were detected with chemical classifications: benzenoids, alkylbenzenes, esters, thioesters, sulfur compounds, amines, organosilicon, alcohols, diakyl ketone, methyl ketone, sulfides, sulfide thioesters, and ketone sulfones. Ten compounds were selected based on GC peak area. Commercially available counterparts of selected VOCs were indirectly applied using concentrations at 1 mM, 10 mM, 100 mM, and 1 M. Shoot dry weight was greater when rice seedlings were exposed to the commercially purchased 1-Butanol, 2-methyl-, (S)- (2 MB), detected in the HS-SPME/GC–MS of Stenotrophomonas sp. broth culture. Element analysis revealed significantly higher Mn, Fe, Zn shoot concentration in the rice seedlings exposed to 2 MB compared to seedlings grown in 100 mM NaCl without VOC exposure. The seedlings grown in 100 mM NaCl also had lower K, Ca, Mg, P, and Cu shoot element concentrations. Significant relative gene expressions of OsYSL15 , OsNAS1 , OsNAS2, and OsRMC were observed in shoot rice seedlings exposed to 2 MB in saline conditions. Thus, indirect interaction of environmental bacteria can influence plant physiology via microbial volatile organic compounds.

Activation of α7 nicotinic acetylcholine receptor augments nerve growth factor action on PCtrk cells - T. Mutoh; Y. Niimi; Akihiro Ueda (Toxicology, 2024)

Correction to: Common findings of blaCTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2019)

Effects of Transcranial Direct Current Stimulation of the Posterior Parietal Cortex on the Control of Visual Attention - Y. Hirakawa; K. Takeda; S. Tanabe; S. Koyama; T. Ueda; K Morishima; M. Iwai; S. Kuno; I. Motoya; H. Sakurai; Y. Kanada (Neurophysiology, 2019)

The behavioural homing response of adult chum salmon Oncorhynchus keta to amino‐acid profiles - E. Y. Chen; J. B. K. Leonard; H. Ueda (Journal of Fish Biology, 2017)
Adult chum salmon Oncorhynchus keta homing behaviour in a two‐choice test tank (Y‐maze) was monitored using a passive integrated transponder (PIT)‐tag system in response to river‐specific dissolved free amino‐acid ( DFAA ) profiles and revealed that the majority of O. keta showed a preference for artificial natal‐stream water and tended to stay in this maze arm for a longer period; natal‐stream water was chosen over a nearby tributary's water, but not when the O. keta were presented with a non‐tributary water. The results demonstrate the ability of O. keta to discriminate artificial stream waters containing natural levels of DFAA .

Common findings of bla CTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2017)

Enhanced loading regimen of teicoplanin is necessary to achieve therapeutic pharmacokinetics levels for the improvement of clinical outcomes in patients with renal dysfunction - T. Ueda; Y. Takesue; K. Nakajima; K. Ichiki; A. Doita; Y. Wada; T. Tsuchida; Y. Takahashi; M. Ishihara; H. Ikeuchi; M. Uchino; T. Kimura (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Hydrogeochemistry and quality of surface water and groundwater in the vicinity of Lake Monoun, West Cameroon: approach from multivariate statistical analysis and stable isotopic characterization - Brice T. Kamtchueng; Wilson Y. Fantong; Mengnjo J. Wirmvem; Rosine E. Tiodjio; Alain F. Takounjou; Jules R. Ndam Ngoupayou; Minoru Kusakabe; Jing Zhang; Takeshi Ohba; Gregory Tanyileke; Joseph V. Hell; Akira Ueda (Environmental Monitoring and Assessment, 2016)

Biological index of environmental lead pollution: accumulation of lead in liver and kidney in mice - T. Takano; Y. Okutomi; M. Mochizuki; Y. Ochiai; F. Yamada; M. Mori; F. Ueda (Environmental Monitoring and Assessment, 2015)

A deletion in a cis element of Foxe3 causes cataracts and microphthalmia in rct mice - Kenta Wada; Yukiko Y. Maeda; Kei Watanabe; Tatsuya Oshio; Takuya Ueda; Gou Takahashi; Michinari Yokohama; Junichi Saito; Yuta Seki; Sumiyo Takahama; Rie Ishii; Hiroshi Shitara; et al. (Mammalian Genome, 2011)

Sources of Information that Promote Breast and Cervical Cancer Knowledge and Screening Among Native Hawaiians in Southern California - Jacqueline H. Tran; Michele Mouttapa; Travers Y. Ichinose; Jane Ka’ala Pang; Dawn Ueda; Sora Park Tanjasiri (Journal of Cancer Education, 2010)

Relationship between the riverine nitrate–nitrogen concentration and the land use in the Teshio River watershed, North Japan - Nina Y. Ileva; Hideaki Shibata; Fuyuki Satoh; Kaichiro Sasa; Hiroshi Ueda (Sustainability Science, 2009)

Effects of external and surgically implanted dummy radio transmitters on mortality, swimming performance and physiological status of juvenile masu salmon Oncorhynchus masou - Y. Makiguchi; H. Ueda (Journal of Fish Biology, 2009)
The effects of external and surgically implanted radio transmitters on juvenile masu salmon Oncorhynchus masou were examined. External attachment of transmitters significantly decreased the survival of fish and caused a decreased critical swimming speed compared with surgical implantation. Although plasma cortisol, plasma glucose and haematocrit values did not differ significantly among groups, it appeared that the most suitable transmitter attachment method for juvenile O. masou may be surgical implantation.

Migratory behaviour of adult chum salmon, Oncorhynchus keta , in a reconstructed reach of the Shibetsu River, Japan - Y. MAKIGUCHI; H. NII; K. NAKAO; H. UEDA (Fisheries Management and Ecology, 2008)
During 2004–2006, 30 adult chum salmon, Oncorhynchus keta (Walbaum), were tagged with electromyogram (EMG) transmitters and depth/temperature loggers and tracked along both the channelised and reconstructed segments of the Shibetsu River, Japan to assess the effects of the river re‐meandering construction on upstream migration. Holding time of chum salmon in the reconstructed segment was longer than in the channelised segment. Further, greater diversity of physical condition in water velocity was observed in the reconstructed segment in 2005. Swimming speeds decreased during holding and often exceeded the critical swimming speed ( U crit ). It appears that the physical characteristics developed in the reconstructed segment may be suitable for holding of chum salmon. Further, swimming speed exceeding U crit prior to holding may be exhaustive so holding behaviour may be important for muscle recovery as well as for efficient swimming to reduce the energetic cost during upstream migration.

Unique grouping of the Far East Asian begomovirus complex based on sequence analyses of the DNA-A genome and associated DNAβ satellite molecules isolated from tomato, honeysuckle and Eupatorium plants in Japan - S. Ueda; M. Onuki; K. Hanada; Y. Takanami (Archives of Virology, 2008)

Collagen type I matrix affects molecular and cellular behavior of purified porcine dental follicle cells - S. Tsuchiya; M. J. Honda; Y. Shinohara; M. Saito; M. Ueda (Cell and Tissue Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Upstream migration of adult chum and pink salmon in the Shibetsu River - Y. Makiguchi; H. Nii; K. Nakao; H. Ueda (Hydrobiologia, 2007)

Bovine and water buffalo Mx2 genes: polymorphism and antiviral activity - H. A. E. Babiker; Y. Nakatsu; K. Yamada; A. Yoneda; A. Takada; J. Ueda; H. Hata; T. Watanabe (Immunogenetics, 2006)

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity - T. Seyama; J. H. Ko; M. Ohe; N. Sasaoka; A. Okada; H. Gomi; A. Yoneda; J. Ueda; M. Nishibori; S. Okamoto; Y. Maeda; T. Watanabe (Biochemical Genetics, 2006)

Molecular mechanisms involved in anti-inflammatory effects of proton pump inhibitors - O. Handa; N. Yoshida; N. Fujita; Y. Tanaka; M. Ueda; T. Takagi; S. Kokura; Y. Naito; T. Okanoue; T. Yoshikawa (Inflammation Research, 2006)

Complete nucleotide sequence of the genomic RNA of an Amami-O-shima strain of East Asian Passiflora potyvirus - H. Iwai; R. Terahara; Y. Yamashita; S. Ueda; M. Nakamura (Archives of Virology, 2006)

Roles of Aquaporin-3 Water Channels in Volume-Regulatory Water Flow in a Human Epithelial Cell Line - H. Kida; T. Miyoshi; K. Manabe; N. Takahashi; T. Konno; S. Ueda; T. Chiba; T. Shimizu; Y. Okada; S. Morishima (The Journal of Membrane Biology, 2005)

Heme oxygenase-1 inhibits cigarette smoke-induced increase in the tracheal mucosal permeability in guinea pigs in vivo - A. Tagawa; T. Kaneko; T. Shinohara; A. Ueda; T. Sato; Y. Ishigatsubo (Inflammation Research, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Comparative analyses of serum vitellogenin levels in male and female Reeves' pond turtles ( Chinemys reevesii ) by an immunological assay - Y. Ueda; H. Hoshi; T. Uemura; Y. Kamata; N. Tada; M. Saka (Journal of Comparative Physiology B, 2004)

Mapping of quantitative trait loci associated with ultraviolet-B resistance in rice (Oryza sativa L.) - T. Sato; T. Ueda; Y. Fukuta; T. Kumagai; M. Yano (Theoretical and Applied Genetics, 2003)

Merging of multiple signals regulating Δ9 fatty acid desaturase gene transcription in Saccharomyces cerevisiae - Y. Nakagawa; A. Ueda; Y. Kaneko; S. Harashima (Molecular Genetics and Genomics, 2003)

Amino acids in stream water are essential for salmon homing migration - T. Shoji; Y. Yamamoto; D. Nishikawa; K. Kurihara; H. Ueda (Fish Physiology and Biochemistry, 2003)

Detection of Japanese yam mosaic virus by RT-LAMP - S. Fukuta; T. Iida; Y. Mizukami; A. Ishida; J. Ueda; M. Kanbe; Y. Ishimoto (Archives of Virology, 2003)

Characteristics of a rice beer (zutho) and a yeast isolated from the fermented product in Nagaland, India - Y. Teramoto; S. Yoshida; S. Ueda (World Journal of Microbiology and Biotechnology, 2002)

General Utility of the Chicken βB1-Crystallin Promoter to Drive Protein Expression in Lens Fiber Cells of Transgenic Mice - Jennifer R. Taube; Chun Y. Gao; Yoji Ueda; Peggy S. Zelenka; Larry L. David; Melinda K. Duncan (Transgenic Research, 2002)

Renal damage and salt-dependent hypertension in aged transgenic mice overexpressing endothelin-1 - T. Shindo; H. Kurihara; K. Maemura; Y. Kurihara; O. Ueda; H. Suzuki; T. Kuwaki; K.-H. Ju; Y. Wang; A. Ebihara; H. Nishimatsu; N. Moriyama; et al. (Journal of Molecular Medicine, 2002)

Distribution of CH 4 in the north basin of Lake Biwa and tributary rivers - Y. Yamada; T. Koitabashi; T. Ueda; E. Wada (Limnology, 2001)

Second record of Cyclopina kiraensis , a small, brackish-water cyclopoid copepod, in Japan - H. Ueda; S. Ohtsuka; Y. Seike; S. Ohtani (Limnology, 2001)

Metabolism of 2-Nitrofluorene, an Environmental Pollutant, and 2-Acetylaminofluorene in Fish - O. Ueda; S. Kitamura; Y. Huruse; T. Saito; Y. Kanzaki; Y. Yano; K. Tatsumi; S. Ohta (Bulletin of Environmental Contamination and Toxicology, 2001)

Nephrotoxicity of D -propargylglycine in mice - R. Konno; M. Ikeda; K. Yamaguchi; Y. Ueda; A. Niwa (Archives of Toxicology, 2000)

Human cytotoxic T-lymphocyte responses specific for peptides of the wild-type Wilms' tumor gene ( WT1 ) product - Y. Oka; O. A. Elisseeva; A. Tsuboi; H. Ogawa; H. Tamaki; H. Li; Y. Oji; E. H. Kim; T. Soma; M. Asada; K. Ueda; E. Maruya; et al. (Immunogenetics, 2000)

”In vivo cryotechnique" in combination with replica immunoelectron microscopy for caveolin in smooth muscle cells - I. Takayama; N. Terada; T. Baba; H. Ueda; Y. Kato; Y. Fujii; S. Ohno (Histochemistry and Cell Biology, 1999)

Allelic diversity at class II DRB1 and DQB loci of the pig MHC ( SLA ) - T. Hosokawa Kanai; Y. Tanioka; M. Tanigawa; Y. Matsumoto; S. Ueda; T. Onodera; Y. Matsumoto (Immunogenetics, 1999)

Detailed Distribution of Accelerating Foreshocks before a M 5.1 Earthquake in Japan - K. Yamaoka; T. Ooida; Y. Ueda (Pure and Applied Geophysics, 1999)

The effects of selenium deficiency on differentiation, degradation, dand cell lysis of L8 rat skeletal muscle cells - Y. Ueda; P. D. Whanger; N. E. Forsberg (Biological Trace Element Research, 1999)

Protein kinase C-independent correlation between P-glycoprotein expression and volume sensitivity of Cl− channel - A. Miwa; K. Ueda; Y. Okada (The Journal of Membrane Biology, 1997)

Genomic organization and chromosomal localization of the human casein gene family - Y. Fujiwara; M. Miwa; M. Nogami; K. Okumura; T. Nobori; T. Suzuki; M. Ueda (Human Genetics, 1997)

Naturally occurring dual infection with human and bovine rotaviruses as suggested by the recovery of G1P8 and G1P5 rotaviruses from a single patient - O. Nakagomi; Y. Isegawa; R. L. Ward; D. R. Knowlton; E. Kaga; T. Nakagomi; S. Ueda (Archives of Virology, 1994)

A new typing method for the avian infectious bronchitis virus using polymerase chain reaction and restriction enzyme fragment length polymorphism - Z. Lin; A. Kato; Y. Kudou; S. Ueda (Archives of Virology, 1991)

Typing of recent infectious bronchitis virus isolates causing nephritis in chicken - Z. Lin; A. Kato; Y. Kudou; K. Umeda; S. Ueda (Archives of Virology, 1991)